2013
DOI: 10.1371/journal.pone.0077173
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Stress and Light-Stress Induce Different Cellular Pathologies in the Symbiotic Dinoflagellate during Coral Bleaching

Abstract: Coral bleaching is a significant contributor to the worldwide degradation of coral reefs and is indicative of the termination of symbiosis between the coral host and its symbiotic algae (dinoflagellate; Symbiodinium sp. complex), usually by expulsion or xenophagy (symbiophagy) of its dinoflagellates. Herein, we provide evidence that during the earliest stages of environmentally induced bleaching, heat stress and light stress generate distinctly different pathomorphological changes in the chloroplasts, while a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 61 publications
6
77
0
1
Order By: Relevance
“…the applied heating rate in the experimental setup. Low heating rates profoundly delay the physiological response of the coral holobiont (Middlebrook et al, 2010) and the ramping rate of 1°C day -1 used in the current study is considerably slower than in previous studies of antioxidant responses under thermal stress; these applied heating rates ranging from near-instantaneous to 4°C hour -1 (Yakovleva et al, 2004;Richier et al, 2005;Higuchi et al, 2008;Yakovleva et al, 2009;Higuchi et al, 2012;Downs et al, 2013;T. Higuchi and I. Yakovleva, personal communication).…”
Section: Tablementioning
confidence: 64%
See 1 more Smart Citation
“…the applied heating rate in the experimental setup. Low heating rates profoundly delay the physiological response of the coral holobiont (Middlebrook et al, 2010) and the ramping rate of 1°C day -1 used in the current study is considerably slower than in previous studies of antioxidant responses under thermal stress; these applied heating rates ranging from near-instantaneous to 4°C hour -1 (Yakovleva et al, 2004;Richier et al, 2005;Higuchi et al, 2008;Yakovleva et al, 2009;Higuchi et al, 2012;Downs et al, 2013;T. Higuchi and I. Yakovleva, personal communication).…”
Section: Tablementioning
confidence: 64%
“…While our study does not provide any further insights into the wellknown synergistic effects of light and temperature on bleaching physiology (Lesser et al, 1990;Lesser and Farrell, 2004;Downs et al, 2013), because we did not actively manipulate irradiance, it is notable that Day 5 in our experiment had the lowest mean irradiance, highlighting that elevated temperature was the primary stressor to induce the bleaching cascade in this experiment. From an ecological perspective, mass bleaching events, affecting multiple species across latitudinal and depth gradients, are primarily driven by anomalies in temperature rather than light (McWilliams et al, 2005;Sammarco et al, 2006;Eakin et al, 2009).…”
Section: Oxidative Stress As a Light And Temperature Response In Hostmentioning
confidence: 86%
“…Recent works (Reynolds et al, 2008;Roberty et al, 2014;Aihara et al, 2016) have indicated the possibility that singlet oxygen production is generated when PQ pool is reduced, i.e., the relative size of oxidized PQ pool is smaller (and thus charge recombination in PSII reaction centers is promoted), which may be a primary factor in coral bleaching (Vass, 2012;Rehman et al, 2016). Nevertheless, these effects have to be documented individually in corals, where it is known that there are varied responses to similar acute thermal stress scenarios (Downs et al, 2013;Gardner et al, 2017). It is entirely possible that despite the "Achilles Heel" of a heat sensitive Rubisco, different Symbiodinium types have evolved different strategies to cope with this problem, and that the diversity of these strategies account for the different heat sensitivities of corals to coral bleaching.…”
Section: Discussionmentioning
confidence: 99%
“…En estudios detallados de los simbiontes dinoflagelados de los corales, la descomposición de la estructura de los tilacoides en las primeras 48 h a 32 °C, precedió la aparición de las ROS y la ocurrencia de daño oxidativo severo. Después de 72 h de exposición al calor, se observaron los procesos homeostáticos de síntesis de HSPs y de enzimas anti-oxidantes (Downs et al, 2013). La pérdida de electrolitos varía con la edad de los tejidos, el órgano, el estado de desarrollo y la especie.…”
Section: Respuestas De Las Plantas Al Estrés Por Altas Temperaturas Cunclassified